Effect of various ratios of carbohydrate-protein supplementation on resistance exercise-induced muscle damage - Samadi, A.; Gaeini, A. A.; Kordi, M. R.; Rahimi, M.; Rahnama, N.; Bambaeichi, E. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: Previous studies have indicated that exercise-induced muscle damage might be attenuated by coingestion of protein and carbohydrate supplement. The purpose of this study was to compare the effect of three various ratios of carbohydrate-protein (CHO+PRO) supplements on resistance exercise-induced muscle damage indices. METHODS: Twenty-eight untrained male students voluntarily participated in this study and were randomly assigned to one of the four groups: 1) CHO+PRO 2:1 ratio, N.=7; 2) CHO+PRO 3:1 ratio, N.=8; 3) CHO+PRO 4:1 ratio, N.=7; 4) placebo group, N.=6. They performed a single bout of resistance exercise (whole body: 3 set×8-10 reps with 70-75% 1RM), with eccentric concentration. Every group consumed prepared CHO/PRO beverages (9% concentration, 10 mL/kg/bw-1 at different ratios) or the same amount of placebo beverage before and in 15 min intervals during exercise. Blood samples were taken before the exercise bout and also at 1 and 24 h post-exercise. In addition, muscle soreness scores were recorded before and 1, 24, and 48 h postexercise. Repeated measures ANOVA (between-within design) and Bonferroni post hoc test were used to analyze dependent measures (a=0.05). RESULTS: Serum creatine kinase (CK) and myoglobin (Mb) increased in all groups compared with pre-exercise but the significant difference among groups was observed in 24 h postexercise, in a way that both CK and Mb levels were higher in placebo group. Muscle soreness increased for all groups from pre to postexercise, but there was not any significant difference among groups at any time point. CONCLUSION: Findings of this study showed that CHO+PRO decreased serum CK and Mb at 24 h post exercise, but did not affect muscle soreness at any time points after exercise. Moreover, there were no significant differences between various ratios of CHO-PRO supplementation.